THE RELATIONSHIP BETWEEN STUDENTS’ MOTIVATION IN LEARNING SPEAKING AND SPEAKING ABILITY OF ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS NEGERI PADANG ACADEMIC YEAR 2017 - Tio Eka Putra; Ratmanida Ratmanida; Don Narius (Journal of English Language Teaching, 2018)
This research is a quantitative-correlational research that measures the stage of the motivation of the students in learning speaking subject and their speaking ability in English. In addition the population of this research is the under-graduate students of English for education department, Faculty Language and Arts academic year 2017, Universitas Negeri Padang and the sample is chosen by using cluster sampling. Furthermore, the problem backgrounded this research is how the relationship between students’ motivation in learning speaking and the speaking ability. For this research, motivation is treated as the x variable and speaking ability as y variable. The instruments used in this research are questionnaire and test. The questionnaire is used to measure the motivation and test for the speaking ability. The questionnaire used is adapted from the The Attitude/Motivation Test Battery (AMTB) by Gardner. The questionnaire was analyzed by using likert scale and speaking test by using speaking rubrics by Brown. The result of this researchshows that there is a relationship between the motivation and speaking ability of tye students. It is shown by the correlational coefficient (rxy) with number 0,002. However, the relationship is not significant because when it is compared with rtable with (α) 5%, the number is 0,3494. It means that rtable > rxy. Thus, it can be concluded that the relationship between x variable and y variable is not significant, Keywords: speaking ability, motivasion, correlational research